Proceedings of the 24th Australian Computer-Human Interaction Conference 2012
DOI: 10.1145/2414536.2414556
|View full text |Cite
|
Sign up to set email alerts
|

Colour coding the fridge to reduce food waste

Abstract: This paper introduces the first iteration of a study aimed at grouping similar food types together in a refrigerator to increase the awareness of available foods for consumers in a domestic environment. The goals of the project are twofold: i) Raise the awareness of available foods for all members of a household; ii) Reduce the amount of expired food waste in the household. The project implemented a paper-based colour scheme in refrigerators in households, assigning colours to particular food types (e.g. green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 5 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…The findings indicate systematic storage is not a common practice amongst our participants. The virtual colour code scheme was found not to be as effective as the physical colour code scheme (Farr-Wharton, Foth et al, 2012) in reducing food waste. One explanation suggests the app requires the user to observe the colour code scheme via EatChaFood before placing food in the systematic location.…”
Section: Impact On Food Supply and Location Knowledgementioning
confidence: 85%
See 1 more Smart Citation
“…The findings indicate systematic storage is not a common practice amongst our participants. The virtual colour code scheme was found not to be as effective as the physical colour code scheme (Farr-Wharton, Foth et al, 2012) in reducing food waste. One explanation suggests the app requires the user to observe the colour code scheme via EatChaFood before placing food in the systematic location.…”
Section: Impact On Food Supply and Location Knowledgementioning
confidence: 85%
“…Secondly, it provides users with a colour code scheme to improve systematic storage within their fridge. Users customise the colours representing foods on their fridge shelving, as described by Farr-Wharton, Foth et al (2012). Thirdly, a shared space named 'Fridgescope' (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a time span between the moment of being informed and the actual moments when a decision is made, this strategy could be ineffective. 2) Human computer interaction: In [31] it was suggested that using the color code scheme in the refrigerator reduces the amount of expired food waste by increasing the awareness of available foods in the refrigerator for all members in a household. Clear et al [32] evaluated the potential of design interventions for the practice of cooking.…”
Section: B Current Solutions For Food Waste Prevention 1) Public Cammentioning
confidence: 99%
“…Additionally, DiSalvo and Vertesi [12], Hall, Jones, Richardson, and Hodgson [17], and Fleron and Pederson [16] have all described the potential of visual methods in studies of human computer interaction. More recently, Farr-Wharton, Foth, and Choi [14] and Jarvis, Cameron, and Boucher [21] have used visual methods (particularly photography) to both study and implement HCI design projects. And work in related areas such as computer science education and game design has similarly advocated for more robust visual research methods, including visual ethnography (see, for example, Fincher, Tenenberg, and Robins [15], and Chan [8]).…”
Section: Related Workmentioning
confidence: 99%